PENGARUH LINGKUNGAN KERJA, PENGAWASAN, KOMPETENSI DAN MOTIVASI TERHADAP KINERJA DENGAN VARIABEL KOMPENSASI SEBAGAI VARIABEL INTERVENING PADA PEGAWAI DISHUBKOMINFO KOTA TEGAL - Dessi Rosdiana; Dewi Indriasih (Multiplier: Jurnal Magister Manajemen, 2016)
The success of an organization in achieving its objectives, cannot be separated from the human resources factor. This is because human resources is a key factor to mobilize other resources that exist within an institution. To realize these goals can be achieved by improving the performance of human resources with the many factors that influence it. The purpose of this research is; 1) to analyze empirically significant influence Work Environment, Supervision, Competency, Motivation, Employee Compensation Dishubkominfo to Tegal. 2) To analyze empirically significant influence Work Environment, supervision, competence, motivation, the employee's performance Dishubkominfo Tegal. 3) To determine empirically significant influence as an intervening variable compensation to employee performance Dishubkominfo Tegal. This type of research is explanatory research (explanation) using a quantitative approach. The location of this research is Dishubkominfo Office of Tegal. With the object of study include: 1) Work Environment, 2) Supervision, 3) Competence,               4) Motivation, 5) Performance and Compensation office clerk Dishubkominfo Tegal. Office workers Dishubkominfo population numbered 204 people with various strata covering court clerks, staff and leaders in the ranks Dishubkominfo Office Tegal as the sample is equal to 135 Employees who are civil servants and non-civil servants. The results showed that: 1) Work Environment, competence significantly influence employee compensation Dishubkominfo Tegal is proven. 2) Monitoring Motivation significantly influence employee compensation Dishubkominfo Tegal is not proven. 3) Working Environment Monitoring significant effect on employee performance Dishubkominfo Tegal is proven. 4) Competence Motivation significant effect on employee performance Dishubkominfo Tegal is proven. 5) Compensation as an intervening variable is a significant positive influence between work environment, supervision, competence and motivation to employee performance Dishubkominfo Tegal is proven. Keywords:  Work Environment, Supervision, Competency, Motivation, Performance, Compensation.